Time-domain electromechanical impedance for Structural Health Monitoring - Filho, Jozue Vieira [UNESP]; Baptista, Fabricio Guimarães; Farmer, Justin; Inman, Daniel J. (My University, 2011)
Electromechanical impedance (EMI) technique is a very simple method that can be usefulness in most of Non-Destructive Evaluation (NDE) and Structural Health Monitoring (SHM) systems. A common application of EMI methods is based on computing the frequency response function (FRF), which requires an impedance analyzer or an equivalent impedance measurement system. In this work it is shown that the time response of a piezoelectric sensor such as Lead Zirconate Titanate (PZT) provides information on the electromechanical impedance variation when a monitored structure is damaged. The time domain approach changes the paradigm of SHM systems based on EMI and the results are similar to those obtained using impedance measurements in the frequency domain. The efficiency of this new approach is demonstrated through experiments using an aluminum plate. The results using both the FRF and the time response are obtained and compared, illustrating that the proposed approach is comparatively more sensitive to damage.
Keywords: Electromechanical impedance; Structural Health Monitoring; Time-domain impedance